Using critical state theory for modelling of asphalt mix compaction - Huerne, Henny L. ter (2020)
This paper focuses on modeling of Hot Mix Asphalt (HMA) material behavior during compaction. During compaction the particle configuration inside the HMA is changing from a relatively loose into a denser one while the bitumen is fluid. Initially particle reorientation is easily possible due to the HMA’s loose configuration. The material behavior predominantly falls in the elastic-plastic domain. Critical state theory from soil mechanics is proposed as a basis for modeling this behavior. An extensive laboratory testing program was undertaken using a modified Hveem stabilometer as a tool for parameterization. The program included: different mixtures, different stages of mixture density and different material temperatures. In this paper, we discuss how well the critical state principles suit HMA behavior, and what the critical state material parameters are for HMA with respect to different material temperatures, different compaction stages and different stress states. We show that HMA compaction behavior can be modeled using the critical state theory and that material behavior is bi-linear in the p’:q stress space.